Bridging the Financial Gap: A Financial Literacy Model for Geriatrics in Negros Oriental - Andres, Marites; Tinguha, Lovely; Diputado, Mary Monette; Ybañez, Romario (Journal of Interdisciplinary Perspectives, 2025)
This study aimed to explore the perceptions of geriatrics in Negros Oriental regarding the importance of retirement preparedness practices and financial literacy. Specifically, it sought to develop a financial literacy model tailored to the needs of individuals preparing for retirement, focusing on investment, emergency funds, debt management, income protection, healthcare, and the overall significance of financial literacy. A descriptive quantitative research design was employed, utilizing a survey questionnaire to collect data. The findings revealed a significant relationship between respondents' profiles and retirement preparedness (r = 0.806, p = 0.034, at 0.05 significance level), leading to the rejection of the null hypothesis. Conversely, the relationship between financial practices and retirement preparedness (r = 0.594, p = 0.291, at 0.05 significance level) was insignificant, failing to reject the null hypothesis. The study underscores the importance of strengthening financial literacy and education campaigns to equip individuals with the knowledge and skills necessary for effective retirement planning.